Low-dose caffeine enhances cognitive processing but not physical performance in fatigued taekwondo athletes: a randomized crossover trial - Alisa Nana; Papatsorn Ramyarangsi; Luksika Jamwai; Poomwut Hiranphan; Vorasith Siripornpanich; Amornpan Ajjimaporn (Journal of the International Society of Sports Nutrition)
Background Caffeine is commonly used to combat fatigue and enhance both cognitive and physical performance. However, its effects on neurophysiological responses and sport-specific performance following fatigue induction remain unclear, particularly in combat sports such as Taekwondo. This study investigated the effects of a 200 mg caffeine dose on physiological markers, electroencephalographic (EEG) brainwave activity, auditory P300 event-related potentials (ERPs), and Taekwondo-specific performance following combined mental and physical fatigue.Methods Thirteen male Taekwondo athletes participated in a randomized, double-blind, crossover study with caffeine (CAF) and placebo (PLA) conditions. Measurements were taken at baseline (pre-supplementation), 30 minutes post-supplementation (post-Sup), and after fatigue induction (post-I). Physiological parameters (heart rate, blood glucose, blood lactate, and ratings of perceived exertion), EEG brainwave activity during resting eyes-open conditions, auditory P300 ERPs, and Taekwondo-specific agility (TSAT) were assessed at all time points.Results Caffeine significantly reduced delta wave power at frontal and parieto-occipital sites at post-Sup (p < 0.05), indicating decreased cortical drowsiness; however, this effect was not sustained at post-I (p > 0.05). P300 amplitude significantly increased in the CAF condition compared to PLA from post-Sup to post-I at the central and parietal electrode sites (p < 0.05), while P300 latency remained unchanged (p > 0.05). No significant differences were observed in reaction time, accuracy, or error rate in the auditory oddball task or TSAT performance across conditions (p > 0.05). Similarly, physiological parameters remained unchanged between groups (p > 0.05).Conclusion A single 200 mg dose of caffeine reduced central fatigue and enhanced cognitive processing, as reflected by suppressed delta wave activity at post-Sup and increased P300 amplitude at post-I. However, caffeine did not influence physiological responses or Taekwondo-specific performance. These findings suggest that low-dose caffeine primarily benefits cognitive function rather than physical performance in combat sports. Future studies should explore dose-response relationships and individual variability in caffeine metabolism to optimize its application in competitive settings.